Acceleration mechanics during forward and backward running: A comparison of step kinematics and kinetics over the first 20 m - Uthoff, A.; Zois, J.; Van Den Tillaar, R.; Nagahara, R. (Journal of Sports Sciences, 2021)
Backward running (BR) and forward running (FR) are unique movements utilized by athletes in many sports. Importantly, this investigation provides further insights on BR and benchmarking against more commonly researched FR capacity. Twenty-one collegiate soccer players (age 20.0 ± 0.8 years, body mass 65.6 ± 7.7 kg, body height 1.70 ± 0.07 m) performed maximal effort BR and FR along 20 m of in-ground force platforms. Step kinematics and kinetics were compared between BR and FR over four relative acceleration phases (BR = steps 1-6, 7-12, 13-18 and 19-23; FR = steps 1-4, 5-8, 9-12, 13-15). The primary findings of this study were that BR speeds were 29% slower than FR (p < 0.001), all step kinematics differed between BR and FR (p < 0.01), except contact time from the second to fourth step phases (p > 0.05), and most step kinetics were lower during BR (p < 0.05), with the exceptions of peak vertical force (p > 0.05). These findings indicate that lower running speeds over the acceleration phases of BR appear to be primarily due to lower horizontal ground reaction force application, resulting in shorter stride lengths and decreased flight times compared to FR.